MAIN ISSUES OF THE DEVELOPMENT OF THE TOURISM INDUSTRY IN UZBEKISTAN - Karimov Diyor Mukhtarovich; Azamat Ashrafovich Kadirov (Journals Park Publishing, 2023)
The tourism is one of the fastest growing and profitable sectors of the economy in the world, which, among other things, can act as a link for strengthening international socio-economic, cultural and spiritual ties. To be one of the most important sectors of the country's economy with a rich cultural and historical potential, Uzbekistan shows great interest in the development of this sector of economy and brings it to a higher, world-standard level.
Keywords: tourism, tourism potential, tourism infrastructure, tourism issues, service, route, tourist map, tourism development, transport.